SARS-CoV-2 vaccines, where do we stand? - Fischer, Alain (Comptes Rendus Biologies, 2021)
Vaccination against the SARS-CoV-2, the virus responsible for the Covid-19 pandemic, represents a major infection control strategy in the absence of effective treatment of the disease to date. Unprecedented mobilization has led to the development of a large number of projects, some of which have already been in test in humans for several months. The first efficacy and safety data are expected in the coming weeks. New vaccine technologies are being evaluated (RNA, replicating or non-replicating viral vectors), further increasing the chances of success. The criteria for evaluating vaccines—despite the exceptional speed of their development—must remain rigorous enough to ensure their acceptance by the population. Beyond their development, mass production and equitable distribution raise many questions. Finally, vaccination can only be successfully implemented if health professionals and the population are convinced of its validity, which implies particular attention to the quality of the information given and the methods of communication.